Echoing last words: Luis Camnitzer, Vanessa Place and critical dependency. Issue 9 (21st October 2019) - Toth, Naomi
ABSTRACT: This article explores the political stakes of reprising the last statements of executed offenders as an artistic gesture. Last words represent a potential site of contestation of the sovereign power that is both reflected and constituted in the spectacle of capital punishment. Works of art reprising and recirculating these last words may, but do not necessarily, embody and amplify this disruptive potential. Jacques Derrida has suggested that claims of literary autonomy from the sovereign law in fact rely on the same logics of transcendence and idealisation that sustain the practice of the death penalty. This poses the problem of political commitment: is it possible to engage with the last words of the condemned without perpetuating the logics that underpin the spectacle of capital punishment itself? The figure of Echo, the mythical repeater of the last words of a sentence, might allow us to envisage a position of critical dependency : her repetitions neither transcend nor claim autonomy from the spectacle they partly reproduce, yet they differ from it nonetheless. The works of Luis Camnitzer ( Last Words, 2008) and Vanessa Place ( Last Words, 2015) are examined as examples of critical dependency's minimal potency.